Awareness and acceptance of family planning methods amongst women undergoing MTP: a prospective study in Himalayan region - Sharma, B. R.; Dogra, Poojan; Sharma, Reena; Kaushal, Sushruti (International Journal of Scientific Reports, 2018)
Background: Family planning services have important role in improving the quality of the lives of a couple and their economic welfare. The objective of the study was to assess the level of awareness and acceptance of different family planning methods among women undergoing to medical termination of pregnancy (MTP). Methods: This study was done at IGMC KNSHM&C Shimla on 1168 women who reported for MTP in department of Obstetrics and Gynaecology. This study was conducted to find out the awareness about the contraceptive practices, source of information and knowledge, the most preferred method and impact of MTP on acceptance of contraception. Results: Majority about 97.5% had knowledge about the contraceptive methods and only 2.5% were unaware of any method. Source of information was health and family planning staff. The next source was friends, relatives and mass media, teaching institutions had least role. In spite of knowledge only about 49% were practicing contraception prior to MTP that too OCP and CC only. Conclusions: Majority of women had optimal knowledge but only less than half of them were using contraceptives. Lacuna is still there, we need to educate and motivate couples to improve family planning services. There is a great need to strengthen the awareness, education and communication regarding various family planning methods in women of reproductive age group.